Conflict Analysis of Characters in the Novel Cahaya Di Bawah Cahaya by Helvy Tiana Rosa, Benny Arnas, and Asma Nadia - Safitri, Nurulia; Shomary, Sudirman (UIR Press, 2024)
This research is motivated by a character conflict and dispute that diverts the fate of the characters which tells one aspect of the character's life in the story which refers to the conflict that occurs in a story so that it becomes dramatic and refers to a struggle between balanced forces and implies the existence of counter action. The problems in this research are (1) what is the social conflict of the characters in the novel Cahaya di Bawah Cahaya by Helvy Tiana Rosa et al? (2) what is the internal conflict of the characters in the novel Cahaya di Bawah Cahaya by Helvy Tiana Rosa et al. This research aims to determine and analyze the social and internal conflicts contained in the novel Cahaya di Bawah Cahaya by Helvy Tiana Rosa et al. The theory used is related to social and internal conflict between characters, namely Nurgiyantoro's Fiction Study Theory (2013). The approach in this research uses a qualitative approach with descriptive methods. The data in this research is in the form of quotes containing conflict between characters in the novel Cahaya di Bawah Cahaya by Helvi Tiana Rosa et al. and the data source is the novel Cahaya di Bawah Cahaya by Sequel Hayya. The data collection techniques used are reading techniques, note-taking techniques and concluding techniques. The results of this research show that the most frequently found character conflict is social conflict between characters, quarrels and the least frequently found character conflict is internal conflict, psychosis, which is difficult to distinguish between reality and fantasy that occurs within the character.